2013
DOI: 10.1200/jco.2013.31.15_suppl.3578
|View full text |Cite
|
Sign up to set email alerts
|

Risk of second primary cancers after treatment for locoregional rectal cancer.

Abstract: 3578 Background: The risk of second primary colorectal cancers among rectal cancer patients has been described, but little is known about the risk of non-colorectal malignancies that may occur in the field of radiation. We attempted to quantify the risk, using data from the large population-based California Cancer Registry (CCR). Methods: We analyzed the CCR data for surgically-treated locoregional rectal cancer cases, diagnosed during the period 1988–2009. We excluded cases with second primary tumor (SPT) di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Another was discarded due to no control group [22]. One report with only abstract was excluded [23]. Five papers without separating rectal cancer from colorectal cancer were also excluded [24][25][26][27][28].…”
Section: Literature Searchmentioning
confidence: 99%
“…Another was discarded due to no control group [22]. One report with only abstract was excluded [23]. Five papers without separating rectal cancer from colorectal cancer were also excluded [24][25][26][27][28].…”
Section: Literature Searchmentioning
confidence: 99%
“…These results are consistent with the study reported by Guan et al [ 24 ] who reported that radiation-treated rectal cancer patients had a greater SCR for the bladder than the general population. Another study by Nangia et al [ 25 ] on the estimation of SCR after treatment of rectal cancer has shown that uterine cancer incidence is higher than expected in people who receive pelvic radiation used for treating rectal cancer.…”
Section: Discussionmentioning
confidence: 99%